CLASSIFICATION OF CHILDREN WITH AUTISM SPECTRUM DISORDER - Jurabayeva Barno Rasulbek qizi (Web of Journals Publishing, 2025)
This article provides extensive coverage of the classification of autistic children and the specifics of child development.
Keywords: Autism, asperger's, syndrome, sensor, motor, socialization, mechanism.